Strategic marketing planning - Reed, Peter (Thomson, 2007)
Strategic marketing planning provides a step-by-step guide to each stage of the marketing plan and strategy development process. Featuring a practical and concise approach, this text is an invaluable resource for students and business practitioners charged with the responsibility of developing a strategic marketing plan.